2007
DOI: 10.2134/jeq2006.0319
|View full text |Cite
|
Sign up to set email alerts
|

Remediation of Heavy Metal–Contaminated Forest Soil Using Recycled Organic Matter and Native Woody Plants

Abstract: The main aim of this study was to determine how the application of a mulch cover (a mixture of household biocompost and woodchips) onto heavy metal-polluted forest soil affects (i) long-term survival and growth of planted dwarf shrubs and tree seedlings and (ii) natural revegetation. Native woody plants (Pinus sylvestris, Betula pubescens, Empetrum nigrum, and Arctostaphylos uva-ursi) were planted in mulch pockets on mulch-covered and uncovered plots in summer 1996 in a highly polluted Scots pine stand in sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 41 publications
0
21
1
1
Order By: Relevance
“…and Betula sp. have been proved to reduce adverse environmental impacts and increase the esthetical quality of industrial wasteland (Hüttl and Weber, 2001;Helmisaari et al, 2007;Pietrzykowski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…and Betula sp. have been proved to reduce adverse environmental impacts and increase the esthetical quality of industrial wasteland (Hüttl and Weber, 2001;Helmisaari et al, 2007;Pietrzykowski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This process uses organic materials such as bitumen, polyethylene, paraffins, waxes, and other polyolefins as thermoplastic or thermosetting resins. For polymer encapsulation, the organic materials are heated and mixed with the contaminated matrix at elevated temperatures (120 • to 200 • C). The organic materials polymerize and agglomerate the waste, and the waste matrix is encapsulated [84].…”
Section: Solidification/stabilization (S/s)mentioning
confidence: 99%
“…Phytoremediation, also called green remediation, botanoremediation, agroremediation, or vegetative remediation, can be defined as an in situ remediation strategy that uses vegetation and associated microbiota, soil amendments, and agronomic techniques to remove, contain, or render environmental contaminants harmless [119,120]. The idea of using metal-accumulating plants to remove heavy metals and other compounds was first introduced in 1983, but the concept has actually been implemented for the past 300 years on wastewater discharges [121,122].…”
Section: Phytoremediationmentioning
confidence: 99%
“…Composting during two years was more effective than during one year [92]. It was also shown that a mixture of domestic compost and wood chips caused a natural recolonization in polluted environments with heavy metals, including willow seedlings [93].…”
Section: Impact On Tree Yield and Physiologymentioning
confidence: 99%